PARADIGMA LIBERAL ARTS DALAM PENDIDIKAN DI ERA DISRUPSI STUDI KASUS DI ZAYTUNA COLLEGE - Kurniawan Dwi Saputra (Universitas Muhammadiyah Surakarta, 2020)
Amidst the noisy discourse of disruption era, the orientation of education in Indonesia is in a crossed way. On the one hand, by the presidential regulation number 87 on 2017, the government wants indonesian education to foster its character education. On the other hand, the more pragmatic approach to prepare skill-based system of education as the answer to industrial demands is obvious in the more recent government discourse. Based on this background, this qualitative research tries to present liberal arts education paradigm as an alternative way to today’s form of education. By studying relevant literature resources, and by evaluating its practice in Zaytuna College as the case, this research argues that liberal arts education is in line with core principles in Islamic education which views human as holistic creatures with many potentials.Di tengah hingar bingar perbincangan tentang era disrupsi, orientasi pendidikan di Indonesia berada pada persimpangan jalan. Di satu sisi, berdasarkan peraturan presiden nomor 87 tahun 2017, pemerintah menginginkan pendidikan Indonesia untuk memperkuat pendidikan karakter. Di sisi yang lain, pendekatan yang lebih pragmatis untuk mempersiapkan sistem pendidikan yang menjawab kebutuhan dunia industri sangat jelas pada diskursus-diskursus pemerintah yang lebih baru. Berdasarkan latar belakang ini, penelitian kualitatif ini, mencoba menghadirkan paradigma pendidikan liberal arts sebagai jalan alternatif bagi pola pendidikan hari ini. Melalui studi sumber pustaka yang relevan, serta dengan mengevaluasi praksisnya di Zaytuna College sebagai studi kasus, penelitian ini berargumen bahwa pendidikan liberal arts selaras dengan prinsip-prinsip pokok pendidikan Islam yang memandang manusia sebagai makhluk holistik dengan potensi yang beragam.